The Effect of Jot Thoughts Technique towards Students' Descriptive Text Writing Skill at Eleventh Grade of SMA Swasta Teladan Pematangsiantar - Irma Wardani Turnip; Dumaris Elseria Silalahi; Tiarma Intan Marpaung (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research aims to investigate the effect of Jot Thoughts technique toward students’ descriptive text writing skill at eleventh grade of SMA Swasta Teladan Pematangsiantar. The research method used is a quasi-experiment with two classes, namely the experimental class using Jot Thoughts technique and the control class using conventional technique. The population of this research was grade eleventh of SMA Swasta Teladan Pematangsiantar in the academic year 2024/2025. The researcher took two classes as the sample. The samples were XI-2 as experimental group consisting of 39 students and XI-1 as control group consisting of 39 students. Data were collected through written tests conducted before (pre-test) and after the treatment (post-test). The Jacobs’ writing assessment rubric was used in this research, which includes several aspects namely content, organization, vocabulary, language use and mechanics. The results of data analysis showed that there was a significant improvement in the writing skill of students who use Jot Thoughts technique compared to the control group. The researcher found that the mean score in the experimental pre-test was 52, 69 and the post-test mean was 76,25 while in the control class pre-test mean was 51,30 and the post-test mean was 68,02. The result of t-test was 2,594 which was higher than t-table at 5% of significance level 1,665. The result of significance value indicates that alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. It means that there was a significant effect by using Jot Thoughts technique at eleventh grade of SMA Swasta Teladan Pematangsiantar in writing descriptive text.